Problematika Pelaksanaan Pembelajaran Inklusi di SDN Betet 1 Kediri - Khotimah, Husnul (Ali Muchasan, 2019)
This study aims to reveal the problems that arise when the implementasion of learning in inclusive school take place. Data collection techniques were conducted by interview, documentation, and field observation. Data analysis techniques using analysis of qualitative data verifikatif, that is knowing the hidden meaning behind phenomenon in research location. The result showed that there are four kinds of problem that exist, namely difficulties in modifying curriculum, lack of competence of teachers and students, lack of facilities and infrastructure that support learning and lack of support from parents and community. The solution offered is to increase the number of educators in accordance with the needs of schools and often provide training to them so as to improve the ability to guide students, make relationship with Universities Pshycology Student, establish good relationship between the school and the commitee with the aim to create a good collaboration in realizing the goal of learning the maximum